2016
DOI: 10.7448/ias.19.1.20672
|View full text |Cite
|
Sign up to set email alerts
|

Same day HIV diagnosis and antiretroviral therapy initiation affects retention in Option B+ prevention of mother‐to‐child transmission services at antenatal care in Zomba District, Malawi

Abstract: IntroductionData from the Option B+ prevention of mother-to-child transmission (PMTCT) program in Malawi show considerable variation between health facilities in retention on antiretroviral therapy (ART). In a programmatic setting, we studied whether the “model of care,” based on the degree of integration of antenatal care (ANC), HIV testing and counselling (HTC) and ART service provision–influenced uptake of and retention on ART.MethodsWe conducted a retrospective cohort study of pregnant women seeking ANC at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 12 publications
9
74
2
1
Order By: Relevance
“…The lower retention on ART that we observed among pregnant and breastfeeding women aligns with results of previous studies of Option B+ women in Malawi [24] showing that they were at a higher risk of being lost to follow-up, especially early in the course of ART [24]. Long travel distance to the clinic, lack of transport money, developing side effects, inability to reach the clinic due to severe illness and non-comprehension of ART education [30], ART initiation on the day of HIV testing [31], models of HIV care at the health facility [32] and non-disclosure of HIV status between spouses [33] were identified as barriers for pregnant and breastfeeding mothers to remain engaged in HIV care. Eligibility criteria for ART and HIV management guidelines were the same for pregnant and breastfeeding women before and after UTT implementation in Malawi.…”
Section: Discussionsupporting
confidence: 89%
“…The lower retention on ART that we observed among pregnant and breastfeeding women aligns with results of previous studies of Option B+ women in Malawi [24] showing that they were at a higher risk of being lost to follow-up, especially early in the course of ART [24]. Long travel distance to the clinic, lack of transport money, developing side effects, inability to reach the clinic due to severe illness and non-comprehension of ART education [30], ART initiation on the day of HIV testing [31], models of HIV care at the health facility [32] and non-disclosure of HIV status between spouses [33] were identified as barriers for pregnant and breastfeeding mothers to remain engaged in HIV care. Eligibility criteria for ART and HIV management guidelines were the same for pregnant and breastfeeding women before and after UTT implementation in Malawi.…”
Section: Discussionsupporting
confidence: 89%
“…Given that other observational studies have reported higher risk of attrition in same-day initiates [31, 34], we included this factor in the analysis as a possible predictor of attrition. Although no association was discovered, we still suggest that caution should be taken with same-day ART initiation as a public health approach and patient readiness should be taken into account [35].…”
Section: Discussionmentioning
confidence: 99%
“…More than 12% of the women had no education, 63% were unemployed and 56% were in a couple or married. The median gestational age at ART initiation for the 'B+ pregnant' women was 25 weeks (IQR: [19][20][21][22][23][24][25][26][27][28][29]. The median follow-up time under ART was 13 months (IQR: .…”
Section: Attrition Risk At 12 Months After Art Initiationmentioning
confidence: 99%